Green waqf as an Islamic Economic Instrument to Realize Ecological piety: A Conceptual and Empirical Study : Green waqf as an Islamic Economic Instrument to Realize Ecological piety: A Conceptual and Empirical Study - Zulkarnain Ali; Khalifah Muhammad Ali; Hanifah Ahzami (Jurnal Bimas Islam, 2026)
The global environmental crisis poses multidimensional challenges that demand integrated spiritual, social, and ecological responses. Islam views humans as khalīfah fi al-arḍ (vicegerents on earth) responsible for maintaining balance and prosperity within creation. In this context, green waqf (eco-waqf) emerges as an Islamic economic innovation oriented toward environmental conservation and community empowerment. This study aims to analyze the concept of green waqf from the perspective of Islamic economics and maqāṣid al-syarī‘ah, examine its role in realizing ecological piety, and identify its practical implementation and challenges in Indonesia. Using a qualitative approach through literature review and a case study on the Bogor Forest Waqf Foundation (YWHB), the study finds that green waqf is not merely environmental philanthropy but a manifestation of ecological piety integrating spiritual, social, and economic dimensions. The YWHB has successfully implemented sustainable green waqf practices through conservation, community empowerment, and eco-da’wah programs grounded in maqāṣid al-syarī‘ah, which expands the objectives of Islamic law to include ḥifẓ al-bi’ah (environmental preservation). Theoretically, this study broadens the horizon of Islamic economics toward a spiritually grounded green economy; practically, it provides a sustainable and worship-oriented institutional model for green waqf development.